Keterampilan Menyimak Teks Prosedur Melalui Teknologi Informasi “Tik-Tok” - Dini Septiari, Wahyu (Kawruh: Journal of Language Education, Literature and Local Culture, 2022)
Listening skills for some teachers are more on listening skills, not on listening as a process and mechanics so that skills in technological sophistication are needed as interesting learning media. Technology can be used to help students develop listening skills through information technology, one of which is "Tik-Tok" with various available pages. Each type of technology provides opportunities for students to explore their listening strategies and in some cases develop new strategies. This study uses a descriptive method using a qualitative approach. In this case, the researcher is not directly involved in the object of study but only as an observer of the object of study contained in the contents of the "TikTok" account. The note-taking technique is carried out to record and select the elements that are listened to from social media or information technology "Tik-Tok" in Procedure Text learning then written into data paper. The purpose of the research is that with tiktok media students can observe, listen to technology, besides that listening is not only tangible in writing but with the digital era through tiktok video media students will understand in more detail listening with technology. Development of better listening skills and exploiting old technology or new technology in various ways in order to meet the needs of students in responding to changes and developments in listening learning technology. The conclusion is that listening with technology media provides new insights and new knowledge in listening skills, students are more enthusiastic to understand in depth than listening using technology, students can get to know better and become familiar with technology.